Equilibrium, Kinetics, and Thermodynamics of Methylene Blue Adsorption by Pine Tree Leaves - Yagub, Musstafa; Sen, Tushar; Ang, Ming (Springer, 2012)
The adsorption capacity of pine tree leaves for removal of methylene blue (MB) from aqueous solution was investigated in a batch system. The effects of the process variables, such as solution pH, contact time, initial dye concentration, amount of adsorbent, agitation speed, salt concentration, and system temperature on the adsorption process were studied. The extent of methylene blue dye adsorption increased with increase in initial dye concentration, contact time, agitation speed, temperature, and solution pH but decreased with increased in amount of adsorbent and salt concentration. Equilibrium data were best described by both Langmuir isotherm and Freundlich adsorption isotherm. The maximum monolayer adsorption capacity of pine tree leaves biomass was 126.58 mg/g at 30°C. The value of separation factor, R L , from Langmuir equation and Freundlich constant, n, both give an indication of favorable adsorption. The intrapartical diffusion model, liquid film diffusion model, double exponential model, pseudo-first and second order model were used to describe the kinetic and mechanism of adsorption process. A single stage bath adsorber design for the MB adsorption onto pine tree leaves has been presented based on the Langmuir isotherm model equation. Thermodynamic parameters such as standard Gibbs free energy (ΔG 0), standard enthalpy (ΔH 0), and standard entropy (ΔS 0) were calculated.